HYPOGLYCEMIC EFFECT TEST OF ETHANOLIC EXTRACT OF BALIGO SEEDS (BENINCASA HISPIDA (THUMB.) COGN.) ON WHITE MALE RATS WISTAR STRAIN WITH ALLOXAN INDUCTION - Maryati, Dina; Sarimanah, Jamilah; Herdwiani, Wiwin; Zamzani, Irfan (Jurnal Farmasi Indonesia, 2019)
Baligo is native of tropical regions in Indonesia known as a large gourd or pumpkin. Baligo among others contain carbohydrates, glycosides, alkaloids, phytosterols, gums and mucilago, saponins, proteins and free amino acids, and flavonoids. Chemical constituents in seed baligo which is thought to have anti-diabetic activity of flavonoids and saponins. This study aims to determine the hypoglycemic effect of ethanolic extract of baligo seeds (Benincasa hispida (Thumb.) Cogn.) and find out what the larger dose of ethanolic extract of baligo seeds (Benincasa hispida (Thumb.) Cogn.) the greater hypoglycemic effect on white male rats strain wistar with alloxan induction. This study used a method in which alloxan induced rats were divided into five treatment groups that each group consisted of five rats. Group I as a negative control (CMC 0.5%), Group II as a positive control (glibenclamide) at a dose of 0.09 mg/200 g BB rats, and Group III, IV, V given doses of ethanol extract of seeds baligo 4.10 mg/200 g BB rast, 8.21 mg/200 g BB rats, 16.42 mg/200 g BB rats. All groups alloxan induced on day 0 (after fasting 16 hours) intraperitoneally. Examination of blood sugar levels performed on days 4 and 8 after administration of the test preparation. Statistical analysis showed that the greater the dose of ethanolic extract of baligo seeds (4.10 mg/200 g BB rats, 8.21 mg/200 g BBrats, 16.42 mg/200 g BB rats) was not the greater hypoglycemic effect on white male rats wistar strain with alloxan induced